Ageing and the Relative Price of Nontradeables - Leon Bettendorf; Hans Dewachter (Tinbergen Institute, 2007)
In this paper we identify the effects of ageing on the relative price of nontradeables versus tradeables. We consider two cases. In a first specification, age effects only account for short-run dynamics. An alternative case allows for permanent age effects. Estimating the respective cases by means of an ECM on a panel of OECD countries we find significant effects of demographic composition on the relative prices, even after correcting for the standard explanatory variables. Simulations based on population projections of the UN show that ageing might substantially contribute to inflationary pressures in the near future.
Keywords: F41; E31; J11; 330; relative price of nontradeables; age-specific effects; productivity differentials; Alternde Bevölkerung; Relativer Preis; Nicht-handelbare Güter; Produktivität; OECD-Staaten